The Effect of Service Quality, Consumer Perceptions, and Facilities on Consumer Satisfaction: Case study in Indonesia - Utari, Woro; Indrawati, Mei; Sobakh, Nurus; ., Waras; ., Rusdiyanto (Journal of Ecohumanism, 2024)
This study examines the connections between facilities, customer satisfaction, service quality, and consumer impression. This study uses Ordinary Least Square (OLS) regression, Stata software for data analysis, and a sample of Surabaya hospital customer respondents. The study’s findings demonstrate that while customer perceptions are unaffected, service quality significantly impacts customer satisfaction. Facilities also have a significant and beneficial impact on customer happiness. Amenities, customer perceptions, and service quality heavily affect customer satisfaction. The findings of this study can be used by the government and businesses in Surabaya, Indonesia, to inform policy decisions about hospital patient happiness, service quality, and customer perceptions. This research’s theoretical application can clarify concepts in marketing management and offer factual data regarding the caliber of services: customer pleasure and their opinions of the facilities.